Magnetic resonance imaging pattern recognition of metabolic and neurodegenerative encephalopathies in dogs and cats - Miguel-Garcés, María; Gonçalves, Rita; Quintana, Rodrigo; Álvarez, Patricia; Beckmann, Katrin M.; Alcoverro, Emili; Moioli, Melania; Ives, Edward J.; Madden, Megan; Gomes, Sergio A.; Galban, Evelyn; Bentley, Tim; et al. (Frontiers in Veterinary Science, 2024)
Metabolic/neurodegenerative encephalopathies encompass a wide list of conditions that share similar clinical and magnetic resonance imaging (MRI) characteristics, challenging the diagnostic process and resulting in numerous tests performed in order to reach a definitive diagnosis. The aims of this multicentric, retrospective and descriptive study are: (I) to describe the MRI features of dogs and cats with metabolic/neurodegenerative encephalopathies; (II) to attempt an MRI recognition pattern classifying these conditions according to the involvement of grey matter, white matter or both; and (III) to correlate the MRI findings with previous literature. A total of 100 cases were recruited, comprising 81 dogs and 19 cats. These included hepatic encephalopathy, myelinolysis, intoxications, thiamine deficiency, hypertensive encephalopathy, neuronal ceroid lipofuscinosis, gangliosidosis, fucosidosis, L-2-hydroxyglutaric aciduria, Lafora disease, spongiform leukoencephalomyelopathy and cerebellar cortical degeneration. None of the hepatic encephalopathies showed the previously described T1-weighted hyperintensity of the lentiform nuclei. Instead, there was involvement of the cerebellar nuclei (8/23), which is a feature not previously described. Dogs with myelinolysis showed novel involvement of a specific white matter structure, the superior longitudinal fasciculus (5/5). Thiamine deficiency affected numerous deep grey nuclei with novel involvement of the oculomotor nuclei (3/9), thalamic nuclei, subthalamus and cerebellar nuclei (1/9). Cats with hypertensive encephalopathy had a more extensive distribution of the white matter changes when compared to dogs, extending from the parietal and occipital lobes into the frontal lobes with associated mass effect and increased brain volume. Lysosomal storage disease showed white matter involvement only, with neuronal ceroid lipofuscinosis characterised by severe brain atrophy when compared to gangliosidosis and fucosidosis. All patients with L-2-hydroxyglutaric aciduria had a characteristic T2-weighted hyperintense swelling of the cerebral and cerebellar cortical grey matter, resulting in increased brain volume. Lafora disease cases showed either normal brain morphology (5/11) or mild brain atrophy (6/11). Dogs with cerebellar cortical degeneration had more marked cerebellar atrophy when compared to cats. This study shows the important role of MRI in distinguishing different metabolic/neurodegenerative encephalopathies according to specific imaging characteristics.